Sistem Penegakan Hukum Pencurian Kelapa Sawit Di Wilayah Penajam Paser Utara dalam Perspektif Hukum Pidana di Indonesia - Suradi Suradi; Bachtiar Rasyid Sahidanna; Joni Budiawan (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
This research aims to understand and analyze how criminal law is applied and enforced in the context of palm oil theft cases in the North Penajam Paser area, Indonesia. The focus of this research is on the case of an individual with the initials MY who has repeatedly committed acts of theft on land owned by PT. WKP (Waru Kaltim Plantation), but only received verbal and written warnings. This research uses empirical legal research methods, by collecting primary data through interviews and direct observation in the field, as well as secondary data through the study of relevant literature and legal documents. It is hoped that the results of this research will provide deeper insight into the application of criminal law and how increased effectiveness and fairness in law enforcement can be achieved, especially in cases of criminal acts of palm oil theft. This research also provides recommendations for carrying out reforms in the criminal law enforcement system and adjusting the criminal law framework to handle similar cases in the future so that the results of this research can provide deeper insight into the application of criminal law and how increased effectiveness and fairness in law enforcement can be achieved. achieved, especially in cases of criminal acts of palm oil theft.